A clinical study on ectopic pregnancy in a tertiary care hospital over one year - Khandkar, Sharvari A.; Modi, Rahi; Jain, Mahima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Ectopic pregnancy is a life threatening emergency in obstetrics presenting in the 1st trimester. The incidence is about 1% globally. We have aimed to study the incidence, presentation and management of ectopic pregnancy. Various risk factors were identified which may be helpful in reducing maternal mortality. Methods: A one year retrospective study involving detailed medical records of patients who underwent obstetric hysterectomy between 1st November 2022 and 31st October 2023. Results: The overall incidence of ectopic pregnancy was 0.8% in this study. The incidence was highest in 26-30 year age group (40%) followed by 21-25 year age group (36.4%). 95.2% cases presented with tubal ectopic while 2.4% each of cervical ectopic and caesarean scar ectopic pregnancies. LSCS was the most common risk factor associated with ectopic pregnancy, other risk factors included pelvic inflammatory disease in 33.3% cases, 29.5% patients with infertility treatment. 59% were ruptured ectopic pregnancies, 40% with unruptured ectopic pregnancy and 1% case of chronic ectopic. Multiple signs were seen in majority of patients including tachycardia, hypotension, abdominal tenderness, guarding and rigidity, vaginal forniceal fullness and tenderness. Management included laparotomy (58.8%), laparoscopy (31.7%), dilatation and evacuation (3.5%), medical management (3.5%) and hysterectomy (2.3%). No case of maternal mortality was noted. Conclusions: Ectopic pregnancy is still a major challenge in obstetrical practice because of its bizarre clinical presentation. Maternal outcome depends upon timely diagnosis and urgent management of such patients.